Assessment of the Proportion of Men in the Number of Teaching Staﬀ in Schools - Yu. S. Pinkovetskaya (Статистика и экономика, 2022)
The purpose of the study. One of the urgent problems of the development of the regions of Russia is to increase the efficiency of regional systems of general secondary education. At the same time, it is necessary to take measures to reduce the gender gap in the personnel of modern schools. In order to understand the gender gap that has developed in the regions, it is advisable to conduct a comparative analysis of differences between regions based on specific indicators. At the same time, it is necessary to take into account the existing differentiation of the proportion of male teaching staff by age. The purpose of our study was to evaluate the indicators characterizing the share of male teachers of different age groups in the total number of teaching staff of schools in the regions of Russia. These indicators were the shares of the number of men of five age groups in the total number of school-teachers in these age categories in 2020.Materials and methods. The study used the methodological approach proposed by the author, based on the consideration of specific indicators describing the proportion of male teachers of different ages working in general education schools in the total number of teaching staff of such schools. The study included five stages. The study used official statistical information for all regions of Russia. This information reflects the results of a federal statistical survey conducted by the Ministry of Education of the Russian Federation. The density functions of the normal distribution were used as models. The study used methods of statistical analysis and, in particular, ANOVA. The study carried out mathematical modeling of the distribution of the considered indicators by regions of Russia.Results. The study proved that there is currently a significant feminization of secondary education in our country. The conducted modeling of empirical data demonstrated that the values of indicators characterizing the share of male teachers in the total number of teaching staff of schools depend on the age of teachers. The maximum value of the indicator was noted in the age group up to thirty years. With increasing age, the values of indicators decrease and reach a minimum in the age group from forty to forty-nine years. At an older age, the proportion of male teachers increases. The article discusses the regional features of the formation of the teaching staff of schools. Regions with minimum and maximum values of each of the five indicators were identified.Conclusion. The proposed methodological approach and the results obtained have a scientific novelty, since the assessment of the territorial features of the gender structure of school-teachers in the regions of Russia has not been carried out before. The methodological approach presented in the article to the assessment of the gender structure of the teaching staff of secondary schools based on the proposed methodology can be used in further research.